Analysis of South Korean and Japanese Diplomacy in Cultural Diffusion According To Constructivism By Alexander Wendt's - Aisyah Az-zahra Mukti; Novi Rizka Amalia (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
In the international relations, countries are major actor that influence relations between other actors. As actors, countries use diplomacy as a material of negotiation to achieve their national interests. South Korean and Japanese diplomacy uses the cultural elements of their countries as its foundation. This cultural diplomacy takes the form of Korean Wave and Cool Japan, which introduce the countries' cultures to the global community. They are the result of Wendt's social constructivism structure. Wendt's constructivism has points that are integration with the implementation of Korean Wave and Cool Japan as forms of cultural diplomacy. In this study, the author uses a qualitative research method that focuses on analyzing the relationships between actors that shape Korean Wave and Cool Japan. By this method, the actors of the Korean Wave and Cool Japan can be analyzed as a form of Wendt's constructivism. Through this research, the Korean wave and cool Japan can be understood as one of the results of Alexander Wendt's social constructivism structure. The Korean wave and Cool Japan are soft power, they that have been recognized worldwide for their cultural values. The values and identities of South Korea and Japan are embedded in these two soft powers to introduce the countries and achieve national interests. They use the country's cultural forms as tools of state diplomacy. Overall, the Korean Wave and Cool Japan make cultural diplomacy that are in demand and influential in the global order. A suggestion for further research expands the scope of the study by adding case studies of other countries that also utilize culture as an instrument of soft diplomacy.Â